Identification of Viral Nervous Necrosis (VNN) in Grouper Fish (Epinephelus sp.) by Reverse Transcriptase-Polymerase Chain Reaction - Galingging, Yova Tresya; Sudaryatma, Putu Eka; Julyantoro, Pande Gde Sasmita; Waskita, Alfi Hermawati; Lestari, Artanti Tri; Nurlita, Wahyu (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 1 (2022): ATBESDO - 10.24843/ATBES.2022.v06.i01.p01, 2022)
Viral Nervous Necrosis (VNN) is a Nodaviridae virus-infected snapper and grouper fish, especially in the larval and seed stages targeted eye and nervous organ. Abnormal swimming was shown by fish behavior at the bottom pond. This study aimed to compare the identification of VNN through three different methods of RNA extraction from the organ target and amplification was carried out by Reverse Transcription of cDNA followed by Polymerase Chain Reaction (PCR) and quantitative real-time PCR (qPCR) technique. Herein, The RNA target from the organ from VNN-positive grouper fish samples targeted RNA2 region with 230-bp in electrophoresis gel and 69-bp by TAM-probe from qPCR were successfully converted and amplified from all RNA extraction kits. Different results of VNN amplified-cDNA were RNA extraction methods-dependent. Amplification using Tri Reagent® extraction kit showed the best result, with a large amount of RNA genome with good purity and showed clear results from PCR and qPCR. Furthermore, the sensitivity of RNA extraction methods was different from 50-100 ng total RNA/reaction. It was concluded that all RNA extraction kits can be used for the detection of the VNN genome by PCR and qPCR technique while resulting in different RNA yields. Overall, this study offers suitable methods to extract the VNN genome from grouper fish.